Role of Microfinance for Empowerment of Rural Women in Haryana - Goel, Madan Mohan (Economic Journal of Nepal, 2015)
Women have been the most under-privileged and discriminated strata of Indian society including Haryana. To reduce if not remove discrimination, discontent and deprivation concerning women, microfinance programs have been promoted as an important strategy for their empowerment ever since1976 when Professor Mohammad Yunus of Bangladesh begin experimenting with microcredit and women Self Help Groups. The present article is based on a study conducted in four districts of Haryana State. In total 272 women members of the Self Help Groups have been interviewed with the help of a comprehensive schedule. The empowerment of women has been judged by analyzing the responses of the women beneficiaries in the study. We have observed that microfinance has resulted in empowerment and social justice. It has helped in reducing domestic violence and also helped in anti-alcoholism among the villagers. But could not helped in preventing bigamy and marriage of girls as well as remarriage of widows because of man dominating society in Haryana with Khap Panchayats. To ensure inclusive growth and women empowerment, we need to control corruption, population and inflation which can increase the efficiency and sufficiency of micro financing for self employment. There is a strong case for monitoring and evaluation with good governance (SMART and SIMPLE administration), manpower planning and inflation targeting for achieving the better results in making microfinance under SHGs a success story in India.The Economic Journal of Nepal Vol. 35, No. 4, October-December 2012 (Issue N0. 140)Page: 279-289